2021
DOI: 10.2147/idr.s337699
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality Among Hospitalized COVID-19 Patients at a Tertiary Care Hospital in Ethiopia

Abstract: Background The very unprecedented virus causing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has continued causing catastrophes in economy and loss of human lives. Despite countries’ urgent and resilient public health actions against the COVID-19 pandemic, the disease is causing a large number of deaths. However, predictors of mortality among hospitalized COVID-19 patients have not been well investigated in Ethiopia. Therefore, this study aimed to identify the predictors of mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 92 publications
5
24
0
Order By: Relevance
“…26 However, all the other included studies have reported the CFR. 25,[27][28][29][30][31][32][33][34][35][36][37] Accordingly, the present study confirmed the CFR of COVID-19 in Ethiopia ranges from nearly 1-20% (Table 3).…”
Section: The Proportion Of Case Fatality Ratesupporting
confidence: 77%
See 4 more Smart Citations
“…26 However, all the other included studies have reported the CFR. 25,[27][28][29][30][31][32][33][34][35][36][37] Accordingly, the present study confirmed the CFR of COVID-19 in Ethiopia ranges from nearly 1-20% (Table 3).…”
Section: The Proportion Of Case Fatality Ratesupporting
confidence: 77%
“…In this review, of the total included studies, eight reported the factors contributing to mortality from COVID-19 in the Ethiopian population. 26,28,[30][31][32][33][34]37 As a result, we found that the presence of a high rate of one or more comorbid conditions was significantly associated with COVID-19 mortality and/or poor treatment outcome. 26,28,30,[32][33][34]37 Furthermore, non-modifiable risk factors…”
Section: Factors Contributing To Mortality Among Covid-19 Patientsmentioning
confidence: 73%
See 3 more Smart Citations